Any Friend of the Movement : Networking for Birth Control, 1920-1940 - Meyer, Jimmy Elaine Wilkinson (Book collections on Project MUSE., 2004)
"In the 1920s, a few Cleveland women perceived a need for reliable birth control. They believed that health and social service professionals denied women, especially poor and working-class women, critical health care information. Any Friend of the Movement tells the story of these women, their actions, and the organization they created - the direct forerunner of a modern Planned Parenthood affiliate. The disparate threads of this particular tale include the suicide of a pregnant woman, the gift of a bereaved inventor, smuggling contraceptive supplies across state lines, and sponsoring ice skating galas to fund the work." "Any Friend of the Movement breaks new ground in the history of birth control activism in North America. Meyer argues that private philanthropy and voluntary action on the part of clinics like the Maternal Health Association (MHA) and their clients vitalized the larger movement at its roots and pushed it forward."--Jacket